1984
DOI: 10.1002/ijc.2910340514
|View full text |Cite
|
Sign up to set email alerts
|

Oral contraceptives containing chlormadinone acetate and cancer incidence at selected sites in the German Democratic Republic ‐ A correlation analysis

Abstract: The use of oral contraceptives containing chlormadinone acetate in 1972 by women of 13 districts (out of 15) of the GDR has been related to the incidence of cancer of breast, corpus uteri, and ovary during the period 1961 to 1980. Cancer incidence was represented by cohort parameters showing the risk of the cohorts in relation to each other. No statistically significant association between the two events was noted. Although not significant, our data are consistent with an elevated relative risk for breast canc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
3
0

Year Published

1986
1986
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 19 publications
1
3
0
Order By: Relevance
“…In contrast to this, a study of the use of oral contraceptives containing CMA found an elevated relative risk for breast cancer of 1.3. The authors state that although not statistically significant, the positive correlation observed for breast cancer may be real [11], which is consistent with our stimulatory results. Up to now, there is a paucity of data available regarding the effects of CMA on the proliferation of normal epithelial breast cells.…”
Section: Discussionsupporting
confidence: 94%
“…In contrast to this, a study of the use of oral contraceptives containing CMA found an elevated relative risk for breast cancer of 1.3. The authors state that although not statistically significant, the positive correlation observed for breast cancer may be real [11], which is consistent with our stimulatory results. Up to now, there is a paucity of data available regarding the effects of CMA on the proliferation of normal epithelial breast cells.…”
Section: Discussionsupporting
confidence: 94%
“…These compounds were shown in some studies to cause benign and malignant tumours in beagle dogs. Although both the results of these experiments and their relevance for human breast cancer have been questioned, these products were consequently withdrawn from public use as constituents of OCs in most countries (Vallance & Capel-Edwards, 1971;Giles et al, 1978;Kwaplen et al, 1980;El Etreby et al, 1979, El Etreby & Neumann, 1980Diszfalusy, 1982 From 1970From to 1978, the proportion of users who used products with chlormadinone decreased from 100% to 20% (Nischan & Ebeling, 1984). This variation in exposure provided a unique opportunity to investigate possible relationships between breast cancer and combined OCs with and without chlormadinone as the constituent progestogen.…”
Section: Discussionmentioning
confidence: 99%
“…Although the conclusions based on these experiments have been disputed, they led to a widespread discontinuation of the use of chlormadinone in OCs. In the former German Democratic Republic (GDR) only OCs containing chlormadinone were in use up to 1971 when different types were introduced (Nischan & Ebeling, 1984). This paper reports the results of a case-control study which is part of the WHO Collaborative Study of Neoplasia and Steroid Contraceptives (1990) aControlled for age; tYTest for trend based on exposed subjects.…”
mentioning
confidence: 99%
“…Of the 5 withdrawn products for which confirmatory studies were conducted in humans, in 4 cases (chlormadinone, fluvoxamine, meclizine, and nitroxoline), the results contrasted with those of the animal research on which withdrawal decisions were based, while the results with the fifth product (zopiclone) were inconclusive (Table ). The difficulty in predicting harms in humans using evidence from animal studies has led to calls from some authors to abandon the use of animals for research …”
Section: Discussionmentioning
confidence: 99%